Transforming Pakistan : ways out of instability - Synnott, Hilary (Abingdon : Routledge for the International Institute for Strategic Studies, 2009)
Analyzes developments in Pakistan's volatile tribal regions, little understood in the West despite their profound implications for regional and international security, and examines the role of past events especially since 11 September 2001 in generating the animosity that many Pakistanis feel towards the West today.
Introduction -- Ch. 1 The nature of Pakistan -- Ch. 2 Pakistan after 9/11 -- Ch. 3 Internal conflicts -- Ch. 4 Regional relationships: India, China, Saudi Arabia and the Gulf -- Prospects and policies.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Pakistan -- Politics and government -- 1988-; Pakistan -- Foreign relations; Electronic books